TAFSIR Q.S AN-NISA : 34 TENTANG KONSEP KEPEMIMPINAN RUMAH TANGGA PERSPEKTIF AL-THABARI - Habibah, Nuraini (IAINU Kebumen Prodi IAT, 2022)
The family is the smallest unit in a nation, but even so the family has a central role in the sustainability of an advanced and prosperous nation. To carry out this central role, a family needs an ideal leader. In Islam, household leadership rests on the shoulders of men, because men have advantages over women and men are responsible for providing for women (QS, Nisa: 34). Ath-Tabari interprets the advantages of men over women in terms of physical, intellectual, skills, work and social. This kind of interpretation was relevant at the time considering that women at that time did not have those advantages. If applied to the current era where many women already have these advantages, not even a few women outperform men both intellectually, economically and socially, then At-Tabari's interpretation becomes less relevant. Based on this fact, it is necessary to develop an interpretation related to the household leadership relation.